Seasonal dynamics and risk assessment of antibiotic resistome in straw-retained agroecosystems - Yi Wu; Yi Fan; Yiheng Tao; Quankuan Guo; Shuang Pang; Wei Yang; Ximei Zhang (Ecotoxicology and Environmental Safety)
Straw retention (SR) is an essential management practice of sustainable agriculture. However, the seasonal dynamics on the antibiotic resistome and associated ecological risks in seasonally frozen agroecosystems remain unclear. Here, we conducted a multi-site field study in the Sanjiang Plain, a seasonally frozen agricultural region of Northeast China, combining time-series soil sampling with metagenomic sequencing to reveal antibiotic resistome dynamics. SR elevated relative abundance of antibiotic resistance genes (ARGs) across all seasons and induced significant seasonal variations in richness. ARG richness peaked during freezing season favoring the dominance of low-risk ARGs. The soil C/N ratio emerged as the primary driver shaping the relative abundance and diversity of antibiotic resistome, with 23 core low-risk ARGs accounting for 73 % of the observed abundance increase, whereas high-risk ARGs constituted merely 0.44 % of the total resistome abundance. Straw retention also reduced interactions among high-risk ARGs with ecological risk remaining stable, demonstrating decoupling between resistome abundance and environmental risk. Structural equation modeling revealed straw retention exerting both direct effects (0.45) and indirect regulation (-0.16) via modulating nutrient content. Our findings evaluated the antibiotic resistance risks of straw retention with the enrichment of low-risk ARGs and suppression of interactions among high-risk ARGs, promoting its safe adoption in agroecosystems. Overall, this study provides a comprehensive antibiotic risk assessment framework, demonstrating straw retention as a beneficial strategy that enhances soil fertility with practically manageable resistance risks in agroecosystems.